ผลของสารสกัดจากแก่นฝาง ชาเขียว และเปลือกมังคุดต่อการลดปริมาณแบคทีเรีย และการชะลออัตราการย่อยแป้งในผลิตภัณฑ์ขนมจีน - Laikhong, Julalux; Phatphaeo, Chutimon; Ratanawimarnwong, Nuanlaor; Songsrirote, Kriangsak; ดอนพุดซา สุเชาว์ (วารสารหน่วยวิจัยวิทยาศาสตร์ เทคโนโลยี และสิ่งแวดล้อมเพื่อการเรียนรู้ (Journal of Research Unit on Science, Technology and Environment for Learning), 2021)
Effect of Extracts from Sappan Core, Green Tea, and Mangosteen Peel on Reduction of the Amount of Bacteria and Retardation of the Starch Digestion Rate in Rice Noodles Julalux Laikhong, Chutimon Phatphaeo, Nuanlaor Ratanawimarnwong, Kriangsak Songsrirote and Suchao Donpudsa รับบทความ: 30 มกราคม 2564; แก้ไขบทความ: 4 มิถุนายน 2564; ยอมรับตีพิมพ์: 16 มิถุนายน 2564; ตีพิมพ์ออนไลน์: 3 ธันวาคม 2564 บทคัดย่อ สารสกัดสมุนไพรจากแก่นฝาง ชาเขียว และเปลือกมังคุดถูกใช้เป็นส่วนผสมในเส้นขนมจีน โดยมีวัตถุประสงค์เพื่อลดปริมาณแบคทีเรียในเส้นขนมจีนเพื่อยืดอายุการเก็บรักษา รวมทั้งช่วยชะลออัตราการย่อยแป้งไปเป็นน้ำตาลเพื่อสุขภาพที่ดีของผู้บริโภคที่ต้องการควบคุมปริมาณน้ำตาลในเลือด โดยนำสารที่สกัดได้จากแก่นฝาง ชาเขียว และเปลือกมังคุดที่ความเข้มข้นต่าง ๆ มาผสมกับแป้งขนมจีน และนำไปขึ้นรูปเป็นเส้นขนมจีน จากนั้นนำเส้นขนมจีนที่ได้ไปหาปริมาณแบคทีเรียที่พบ ณ เวลาต่าง ๆ เทียบกับขนมจีนที่ไม่ผสมสารสกัด รวมทั้งนำเส้นขนมจีนที่ได้มาจำลองระบบการย่อยอาหารของระบบทางเดินอาหารของมนุษย์ในหลอดทดลอง เพื่อตรวจวัดปริมาณของน้ำตาลรีดิวซ์ที่เกิดจากการย่อยเส้นขนมจีน ณ เวลาต่าง ๆ ผลการทดลองพบว่า ขนมจีนที่ผสมสารสกัดสมุนไพรแก่นฝาง ชาเขียว และเปลือกมังคุดสามารถลดปริมาณแบคทีเรียที่พบในขนมจีนได้ โดยขนมจีนที่ผสมสารสกัดจากชาเขียวสามารถชะลอการเจริญของแบคทีเรียในขนมจีนได้ดีกว่าขนมจีนที่ผสมสารสกัดชนิดอื่น นอกจากนี้ยังพบว่า ขนมจีนที่ผสมสารสกัดสมุนไพรแก่นฝางและเปลือกมังคุดต้องใช้ปริมาณสารสกัดค่อนข้างสูงเพื่อชะลออัตราการย่อยเส้นขนมจีนไปเป็นน้ำตาล อย่างไรก็ตามความสามารถในการชะลออัตราการย่อยเส้นขนมจีนไปเป็นน้ำตาลอยู่ได้ไม่เกิน 60 นาที แต่ขนมจีนผสมสารสกัดชาเขียวให้ผลทดสอบดีกว่าขนมจีนผสมสารสกัดแก่นฝางและเปลือกมังคุด โดยสามารถลดอัตราการย่อยแป้งในหลอดทดลองได้ถึง 180 นาที หากเพิ่มความเข้มข้นของสารสกัดชาเขียวให้สูงขึ้น ประสิทธิภาพในการลดอัตราการย่อยแป้งในหลอดทดลองจะสูงขึ้น การใช้สารสกัดจากสมุนไพรโดยเฉพาะแก่นฝาง ชาเขียว และเปลือกมังคุดในขนมจีนจึงมีความเป็นไปได้ที่ใช้ในการชะลออัตราการเจริญของแบคทีเรียในเส้นขนมจีน รวมทั้งช่วยควบคุมปริมาณน้ำตาลในเลือดจากการย่อยเส้นขนมจีนไปเป็นน้ำตาลของผู้ที่มีความเสี่ยงต่อการเป็นโรคเบาหวาน คำสำคัญ: ขนมจีน แก่นฝาง ชาเขียว เปลือกมังคุด การเจริญของแบคทีเรีย อัตราการย่อยแป้ง Abstract Herbal extracts from sappan core, green tea and mangosteen peel were used as an ingredient in rice noodles to reduce the amount of bacteria and increase the shelf–life. They also helped to slow down the rate of starch digestion, which is important for those who want to control the amount of sugar in their blood. The test process started with mixing the substances extracted from sappan core, green tea, and mangosteen peel at different concentrations with rice flour and then using these mixtures to make rice noodles. Experiments were then performed to find the amount of bacteria at different times compared to the rice noodles without the herbal extracts. In addition, tests were performed in a test tube to simulate the digestive system of the human intestines to measure the amount of reduced sugar at different times, and it was found that the rice noodles mixed with herbal extracts from sappan core, green tea, and mangosteen peel could directly reduce the amount of bacteria. However, the rice noodles mixed with the extract from green tea showed the best results for slowing down the growth rate of bacteria compared to mixing with other extracts. In addition, the herbal extracts from sappan core, green tea, and mangosteen peel also helped to slow down the rate of starch digestion. The rice noodles mixed with sappan core and mangosteen peel at high concentration could slow down the rate of digestion of the rice noodles to sugars to around 60 minutes, but green tea extract provided a better result at 180 minutes according to the test tube results. These results showed that the higher the concentration of green tea extract used, the higher the reducing rate in starch digestion. Therefore, the use of herbal extracts, especially sappan core, green tea, and mangosteen peel, in rice noodles is one possible way to slow down the growth of bacteria as well as to control the amount of sugar in the blood from the digestion of rice noodles, which is important for people at risk of diabetes. Keywords: Rice noodles, Sappan core, Green tea, Mangosteen peel, Bacterial growth, Rate of starch digestion